بناء الشخصية في رواية "الأشجار وإغتيال مرزوق" لعبد الرحمن منيف - سكحال خولة (My University, 2024)
Summary: This topic addresses the characterization in the novel "Al-Ashjar wa Ightiyal Murzuq" by Abd al-Rahman Munif, focusing on the role of the character as the primary driving force and central axis of the novel's success. Consequently, the elements within this work encompass the concept of character, its types, methods of presentation, and its various dimensions, all of which contribute to the construction of the novel. The study also explores several dimensions of character, including the physical, psychological, social, and philosophical dimensions, covering both the internal and external construction of characters. ----------------------- ملخص: يعالج هذا الموضوع الذي جاء تحت عنوان بناء الشخصية في رواية الأشجاروإغتيال مرزوق لعبد الرحمن منيف بنية الشخصية الروائية كونها المحرك الرئيسي والمحورالفعال الذي تقوم عليه نجاح الرواية، ومن هذا المنطلق تعددت العناصر داخل هذا العمل شاملة مفهوم الشخصية وأنواعها وطرق تقديمها وأبعادها المختلفة، وكل هذا ساهم في بناء الرواية. كما عالج البحث عدة أبعاد للشخصية متمثلة في البعد الجسمي والبعد النفسي والبعد الإجتماعي والبعد الفكري الفلسفي، أي أننا تطرقنا في هذا البحث إلى كل مايعنى بالشخصية كبناءها الداخلي والخارجي. ----------------------- Résumé : Ce sujet, intitulé "La construction du personnage dans le roman Al-Ashjar wa Ightiyal Marzouq d'Abdul Rahman Munif", aborde la structure du personnage dans le roman comme étant le moteur principal et l'axe effectif sur lequel repose le succès du roman. Dans cette perspective, les éléments à l'intérieur de cette œuvre sont multiples, comprenant le concept du personnage, ses types, ses méthodes de présentation et ses différentes dimensions, tous contribuant à la construction du roman. La recherche aborde également plusieurs aspects du personnage, notamment le physique, le psychologique, le social et le philosophique, en couvrant tous les aspects internes et externes de sa construction.
Keywords: Structure; character; internal construction; external construction; novel.; البنية، الشخصية، البناء الداخلي، البناء الخارجي، الرواية; personnage; construction interne; construction externe; roman.